2013
DOI: 10.1002/iub.1229
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of renal function and structure by the signaling Na/K-ATPase

Abstract: The Na/K-ATPase as an essential ion pump was discovered more than 50 years ago (1,2). The signaling function of Na/K-ATPase has been gradually appreciated over the last 20 years, first from the studies of regulatory effects of ouabain on cardiac cell growth. Several reviews on this topic have been written during the last few years (3–8). This article will focus on the molecular mechanism of Na/KATPase-mediated signal transduction and its potential regulatory role in renal physiology and diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 130 publications
(197 reference statements)
3
39
0
1
Order By: Relevance
“…It integrates an ␣-subunit, responsible for ion movement and various binding sites, and a ␤-subunit, required for the correct enzyme assembly and membrane targeting. Four ␣-isoforms and two ␤-isoforms have been identified: ␣ 1 is ubiquitously expressed, ␣ 2 and ␣ 3 are found in skeletal muscle, neurons, and cardiomyocytes, and ␣ 4 is expressed in testis (149). Besides ion transport function, NKA is a receptor for endogenous cardiotonic steroids (such as ouabain) that trigger several intracellular signal pathways while blocking the ionic transport (149).…”
Section: Healthy Intestinal Tract Epitheliummentioning
confidence: 99%
See 1 more Smart Citation
“…It integrates an ␣-subunit, responsible for ion movement and various binding sites, and a ␤-subunit, required for the correct enzyme assembly and membrane targeting. Four ␣-isoforms and two ␤-isoforms have been identified: ␣ 1 is ubiquitously expressed, ␣ 2 and ␣ 3 are found in skeletal muscle, neurons, and cardiomyocytes, and ␣ 4 is expressed in testis (149). Besides ion transport function, NKA is a receptor for endogenous cardiotonic steroids (such as ouabain) that trigger several intracellular signal pathways while blocking the ionic transport (149).…”
Section: Healthy Intestinal Tract Epitheliummentioning
confidence: 99%
“…Four ␣-isoforms and two ␤-isoforms have been identified: ␣ 1 is ubiquitously expressed, ␣ 2 and ␣ 3 are found in skeletal muscle, neurons, and cardiomyocytes, and ␣ 4 is expressed in testis (149). Besides ion transport function, NKA is a receptor for endogenous cardiotonic steroids (such as ouabain) that trigger several intracellular signal pathways while blocking the ionic transport (149). NKA maintains chemical and electrical gradient between intra-and extracellular spaces, allowing the movement of several ions, most importantly Na Ϫ .…”
Section: Healthy Intestinal Tract Epitheliummentioning
confidence: 99%
“…Studies have found that MBG activated pre-fibrotic signal, which could activate various signaling pathways and EGFR signals by inhibiting NKA, leaded to degeneration of the left ventricular muscle fli-1 and inducing collagen -1 synthesis (Elkareh et al, 2009;Liu et al, 2012;Xie et al, 2013). Study found myocardial fibrosis and siginificant elevation of MBG level in rats with a minipump for infusing MBG and rats had uremia myocarditis (Elkareh et al, 2007).…”
Section: Marinobufagenin and Fibrosismentioning
confidence: 99%
“…Although in the short term, the effect of MBG might balance the high salt load and slow the elevation of blood pressure (Mou et al, 2014), the vasoconstrictive effected by inhibiting NKA may be the long-term response of MBG. In addition, Dietary sodium restriction did not reduce level of plasma MBG (Jablonski et al, 2013).Studies have found that MBG activated pre-fibrotic signal, which could activate various signaling pathways and EGFR signals by inhibiting NKA, leaded to degeneration of the left ventricular muscle fli-1 and inducing collagen -1 synthesis (Elkareh et al, 2009;Liu et al, 2012;Xie et al, 2013). Study found myocardial fibrosis and siginificant elevation of MBG level in rats with a minipump for infusing MBG and rats had uremia myocarditis (Elkareh et al, 2007).…”
mentioning
confidence: 98%
“…Cytosolic [Na + ] overload is accentuated by intracellular acidosis, which induces Na + entry through the NHE. The ischemia associated acidosis contributes to increase cytosolic Ca 2+ induced by the NHE, which is strongly coupled to NCX, so that in long term the cytosolic H + is exchanged with extracellular Ca 2+ [23][24]. Inhibitors of the Na + /H + exchanger were found to be protective if used before ischemia, while their effectiveness was reduced when given during the reperfusion phase [25][26].…”
Section: Effect Of Ischemia/reperfusion In Cardiomyocytesmentioning
confidence: 99%